Human-oriented Leadership And Encouragement To Perform Work: Modelling Organizational Attachment As Mediator. - Yusniati Ishak; Azman Ismail; Asyakireen Samsudin; Umi Hamidaton Mohd Soffian Lee; Mohd Helmi Ali (UKM Press, 2024)
This study investigates the relationship between human-oriented leadership, organizational attachment and encouragement to perform work. A survey method was utilized to collect data from employees at a national election agency in Peninsular Malaysia. The SmartPLS was used to analyze the data and revealed two significant findings: First, relationship between supportive leadership style and organizational attachment was significantly correlated with encouragement to perform work. Second, relationship between participative leadership style and organizational attachment was significantly correlated with encouragement to perform work. The findings endorse that effect of human-oriented leadership on encouragement to perform work is mediated by organizational attachment. Further discussions, implications and conclusion are presented in this study.